Optimization of the Community Rice Barn Program Towards the Pandemic-Affected Community in Palangka Raya City: A Collaboration between Students and Mosque Youth - Kurniawan, Rahmad; Yadi, Andri; Lestari, Diah Ayu; Agusriadi, Ivan Andrians; Nada, Jihan; Hasanah, Laily; Sanawiyah, Sanawiyah; Samsiyah, Samsiyah; Hidayah, Slamet (Institut Teknologi dan Bisnis Asia Malang, 2023)
Purpose: This research paper investigates the Community Rice Barn Program's (Lumbung Beras Rakyat) effectiveness in addressing COVID-19's impact on Palangkaraya City. It analyzes economic vulnerability and food scarcity in pandemic-affected communities. Method: his study combines qualitative interviews and quantitative surveys. Thematic analysis and statistical techniques interpret data on community needs and perceptions of the program's efficacy. Practical Applications: Valuable for policymakers and humanitarian organizations, findings inform the enhancement of pandemic response strategies. Insights promote community resilience and offer guidance for similar programs in different regions. Conclusion: The Community Rice Barn Program significantly alleviates COVID-19's repercussions on Palangkaraya's vulnerable communities. Results emphasize its positive impact on economic well-being and food security, contributing to pandemic mitigation approaches and sustainable development understanding.